Unveiling the contribution of tumor-associated macrophages in driving epithelial-mesenchymal transition: a review of mechanisms and therapeutic Strategies - Zhang, Yijia; Ding, Xiaofei; Zhang, Xue; Li, Ye; Xu, Rui; Li, Hai-Jun; Zuo, Daiying; Chen, Guang (Frontiers in Pharmacology, 2024)
Tumor-associated macrophages (TAMs), fundamental constituents of the tumor microenvironment (TME), significantly influence cancer development, primarily by promoting epithelial-mesenchymal transition (EMT). EMT endows cancer cells with increased motility, invasiveness, and resistance to therapies, marking a pivotal juncture in cancer progression. The review begins with a detailed exposition on the origins of TAMs and their functional heterogeneity, providing a foundational understanding of TAM characteristics. Next, it delves into the specific molecular mechanisms through which TAMs induce EMT, including cytokines, chemokines and stromal cross-talking. Following this, the review explores TAM-induced EMT features in select cancer types with notable EMT characteristics, highlighting recent insights and the impact of TAMs on cancer progression. Finally, the review concludes with a discussion of potential therapeutic targets and strategies aimed at mitigating TAM infiltration and disrupting the EMT signaling network, thereby underscoring the potential of emerging treatments to combat TAM-mediated EMT in cancer. This comprehensive analysis reaffirms the necessity for continued exploration into TAMs’ regulatory roles within cancer biology to refine therapeutic approaches and improve patient outcomes.